Kompetensi Karyawan Pada Trans Studio Bandung - Sukmayadi (Coopetition : Jurnal Ilmiah Manajemen, 2020)
The focus of this study is to describe the competency of employees at the Trans Studio Bandung Departement Show and production. This study aims to describe employee competencies and solutions in dealing with these obstacles. Good employee competency can support the success of a company in achieving its goals. The results obtained show that the competency of Trans Studio Bandung employees is good enough, for knowledge and understanding must be added again seen from the achievement of targets that are still lacking. And for solutions to deal with obstacles employees are able to overcome them well to achieve the work in accordance with expectations, and the company needs to reinstate the appreciation or initiative to employees who have good competence.